The pre-FOMC announcement drift - David O. Lucca; Emanuel Moench (Federal Reserve Bank of New York, 2011)
Since the Federal Open Market Committee (FOMC) began announcing its policy decisions in 1994, U.S. stock returns have on average been more than thirty times larger on announcement days than on other days. Surprisingly, these abnormal returns are accrued before the policy announcement. The excess returns earned during the twentyfour hours prior to scheduled FOMC announcements account for more than 80 percent of the equity premium over the past seventeen years. Similar results are found for major global equity indexes, but not for other asset classes or other economic news announcements. We explore a few risk-based explanations of these findings, none of which can account for the return anomaly.
Keywords: G10; G12; G15; 330; FOMC announcements; equity premium